Microsoft kinect for early education - Tan, Haiwang. (2013)
In recent years, human machine interaction is becoming more and more popular among researchers. A lot of new human machine interaction devices have been developed by various companies in the market. Among all these devices, Microsoft Kinect for XBOX 360 sensor is one of the most popular devices because of its vast penetration and great development support from Microsoft. Kinect sensor is applied widely in research field and video games industry. Currently in the market, there are some video games integrated with Kinect sensor for educational use. However, most of these video games are not customizable and reusable.